Interleukin-2 and Regulatory T Cells in Graft-versus-Host Disease - Koreth, John (2011)
BACKGROUND: Dysfunction of regulatory T (Treg) cells has been detected in diverse inflammatory disorders, including chronic graft-versus-host disease (GVHD). Interleukin-2 is critical for Treg cell growth, survival, and activity. We hypothesized that low-dose interleukin-2 could preferentially enhance Treg cells in vivo and suppress clinical manifestations of chronic GVHD. METHODS: In this observational cohort study, patients with chronic GVHD that was refractory to glucocorticoid therapy received daily low-dose subcutaneous interleukin-2 (0.3×10(6), 1×10(6), or 3×10(6) IU per square meter of body-surface area) for 8 weeks. The end points were safety and clinical and immunologic response. After a 4-week hiatus, patients with a response could receive interleukin-2 for an extended period. RESULTS: A total of 29 patients were enrolled. None had progression of chronic GVHD or relapse of a hematologic cancer. The maximum tolerated dose of interleukin-2 was 1×10(6) IU per square meter. The highest dose level induced unacceptable constitutional symptoms. Of the 23 patients who could be evaluated for response, 12 had major responses involving multiple sites. The numbers of CD4+ Treg cells were preferentially increased in all patients, with a peak median value, at 4 weeks, that was more than eight times the baseline value (P<0.001), without affecting CD4+ conventional T (Tcon) cells. The Treg:Tcon ratio increased to a median of more than five times the baseline value (P<0.001). The Treg cell count and Treg:Tcon ratio remained elevated at 8 weeks (P<0.001 for both comparisons with baseline values), then declined when the patients were not receiving interleukin-2. The increased numbers of Treg cells expressed the transcription factor forkhead box P3 (FOXP3) and could inhibit autologous Tcon cells. Immunologic and clinical responses were sustained in patients who received interleukin-2 for an extended period, permitting the glucocorticoid dose to be tapered by a mean of 60% (range, 25 to 100). CONCLUSIONS: Daily low-dose interleukin-2 was safely administered in patients with active chronic GVHD that was refractory to glucocorticoid therapy. Administration was associated with preferential, sustained Treg cell expansion in vivo and amelioration of the manifestations of chronic GVHD in a substantial proportion of patients. (Funded by a Dana–Farber Dunkin' Donuts Rising Star award and others; ClinicalTrials.gov number, NCT00529035.)